Efektivitas Penggunaan Modul Interaktif Berbasis Problem Based Learning (PBL) pada Mata Kuliah Biologi Umum di Program Studi Pendidikan IPA Institut Pendidikan Nusantara Global - Ermila Mahariyanti; Irwansah (JURNAL ASIMILASI PENDIDIKAN, 2026)
This study aims to determine the effectiveness of the use of interactive modules based on Problem Based Learning (PBL) in the General Biology course in the Science Education Study Program, Institute of Global Nusantara Education. The research design used was a one group pretest-posttest design involving 21 students as research subjects. The instruments used are in the form of multiple-choice test questions and validated descriptions. Data were analyzed using paired sample t-test and N-Gain index to measure improved learning outcomes. The results showed that the average pre-test score was 52.38 and post-test was 79.52 and the results of the hypothesis test with the t-test were <0.05. The average N-Gain obtained was 0.57 which is included in the medium category. As many as 80.95% of students were in the medium N-Gain category and 19.05% in the high category. It can be concluded that PBL-based interactive modules are effective in improving student learning outcomes in General Biology courses.